Impact of Credit on Women Owned Enterprises in Uganda: A Case Study of Mukono Central Division in Mukono District - Brenda Agatha Lwamule (Uganda Christian University, 2024)
This study investigating the impact of credit on women owned enterprises in Mukono Central division, Mukono district, Uganda. The research aims at exploring how access to credit influences the growth, sustainability and empowerment of women owned enterprises in the region. The study employs both qualitative interviews to gather data from a sample of women entrepreneurs operating within the divisions. Quantitative analysis includes assessing the correlation between credit availability and key performance indicators such as revenue growth, employment generation and business expansion. Qualitative interviews delve into the experiences and perceptions of women entrepreneurs regarding credit access, utilization and its implications on their enterprise. The findings from this research contribute to the existing literature on women’s entrepreneurship, examining the financial landscape, socio-economic factors and unique challenges faced by female entrepreneurs providing insights into the roles of credit in fostering economic empowerment and gender equality. Recommendations based on the study’s findings aim to inform policymakers, financial institutions and development agencies on strategies to enhance credit access from women entrepreneurs, thereby promoting inclusive economic growth and sustainable development in Uganda